IMPLEMENTASI PEMENUHAN HAK PEJALAN KAKI TERKAIT JEMBATAN PENYEBERANGAN ORANG (JPO) DI KOTA PEKANBARU - Vionita, Dita; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
As a developing country, Indonesia is a country that has the fourth largest population in the world. With this large population, Indonesia must have a lot of facilities and infrastructure of good quality so that it can be utilized by the community and also support its people in carrying out its activities, especially in big cities, especially Pekanbaru City. The rapid development of the city of Pekanbaru certainly increases the activities of city communities. Likewise with the situation in road traffic, of course, the volume of vehicles also increases. With the increase in the volume of vehicles, the responsibility of the Pekanbaru City government does not stop there, which must also pay attention to the rights of pedestrian communities.This type of research can be classified as sociological jurisdiction, namely a research approach that emphasizes the legal aspects regarding the subject matter to be discussed, related to the realities in the field. This research was conducted in the Regional Representatives Council of the City of Pekanbaru, Pekanbaru City Transportation Department, Pekanbaru City Civil Service Police Unit, while the sample population was the whole party related to the problem under study. Source of data used are primary data and secondary data, data collection techniques in this study are observation, questionnaires, interviews and literature review.In the research result there are three main problems that can be concluded. First, the fulfillment of pedestrian rights related to JPO in Pekanbaru City has not been implemented properly. The second inhibiting factors in fulfilling pedestrian rights are budged factors, official services, unclear rules, JPO standardization and related party coordination. The third attempt by the government in fulfilling pedestrian rights is the need to reform and supervise for the convenience and security of pedestrians, because pedestrians are part of road traffic users who are entitled to good public services.Keywords : Implementation – Pedestrian Rights – Pedestrian Bridge